Acoustic Emission Characteristics and Damage Evolution Analysis of Sandstone under Three-Point Bending Test - Tao Qin; Chen Jiang; Yanwei Duan; Yiwei Wang; Chao Ju (Advances in Materials Science and Engineering)
In order to study the prevention of roadway roof bending, sinking, and breaking and the prevention of dynamic disasters such as the appearance of rock bursts, three-point bending experiments of sandstone under different spans were carried out. By using stress loading system and acoustic emission technology, the acoustic emission characteristic parameters of the sandstone fracture process were analyzed, the precursory information of rock bending fracture was explored, and the evolution law of sandstone damage based on acoustic emission characteristics was obtained. The results showed that according to the variation of acoustic emission ringing count, the load-time curve was divided into four typical stages: the first stage showed an overall increasing trend; the second stage showed an obvious increasing trend; the third stage showed obvious accelerated growth and the acoustic emission ringing count reached the maximum at the moment of rupture. In the fourth stage, the amplitude and frequency of the ringing count are large and high. With the increase in span, the cumulative ringing counts of AE decreased, and the rate of change gradually decreased. The fracture process of three-point bending sandstone can reflect the precursor information of rock fracture from time domain, frequency domain, and R value (ratio of cumulative acoustic emission ringing count to cumulative energy count). In time domain, the evolution characteristics of AE cumulative ringing count stage II can be used to predict the three-point bending fracture of sandstone. The peak frequency shows a linear increase after a spike and then an accelerated increase to a rupture, and the boundary point between the spike and the linear and nonlinear can be obtained. The decrease in R value can indicate that the main crack is growing in the specimen. According to the damage rate, the characteristics of the damage variables can be divided into five stages: stationary and low, gradually increasing, gradually decreasing, main crack coalescence, and complete fracture. With the increase in span, the fracture damage shows a decreasing trend. The residual damage fluctuates between 0.38 and 0.40 due to the difference in crack propagation trajectory. It has theoretical research value for revealing the internal mechanism of rock bending and fracture and has engineering guiding significance for mine pressure and rock strata control and dynamic disaster prevention.